Effect of Dihydropyridine Calcium Channel Blocker on Mortality of Hypertension Patients With Moderate-Severe Pulmonary Acute Respiratory Distress Syndrome: A Multicenter Retrospective Observational Cohort Study. (7th September 2021) - Li, Fengyuan; Gao, Chang; Chen, Jiahao; Yang, Ling; Guo, Shiqi; Jin, Dongmei; Lu, Xiaoting; Sheng, Yin; Ji, Xiaoxia; Guo, Qiang
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: The aim was to evaluate the effect of dihydropyridine calcium channel blocker on the prognosis for moderate-severe pulmonary acute respiratory distress syndrome in hypertension patients. DESIGN: A retrospective, observational, multicenter cohort study. SETTING: A total of 307 patients without propensity score matching and 186 adult inpatients with propensity score matching diagnosed with hypertension and moderate-severe pulmonary acute respiratory distress syndrome in five teaching hospitals in Jiangsu province, China, from December 2015 to December 2020 were enrolled. PATIENTS: A total of 307 patients without propensity score matching and 186 patients with propensity score matching diagnosed with hypertension and moderate-severe pulmonary acute respiratory distress syndrome were included in the final analysis. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Demographic characteristics and clinical characteristics were recorded. The propensity score matching method was used to eliminate the difference between group with dihydropyridine calcium channel blocker and group without dihydropyridine calcium channel blocker. The primary outcome was in-hospital mortality. We used univariate and multivariate regression analyses for both patients with or without propensity score matching to assess the effect of these variables on mortality. In the subset of 186 patients with propensity score matching, in-hospital mortality was 53.2%. Inpatient mortality was significantly higher in patients treated with dihydropyridine calcium channel blocker than in those not treated with dihydropyridine calcium channel blocker of patients without propensity score matching (65.4% vs 40.4%; p < 0.01). Multivariate analysis for patients without propensity score matching showed that dihydropyridine calcium channel blocker (hazard ratio, 1.954; 95% CI, 1.415–2.699), lactate dehydrogenase greater than or equal to 600 U/L (hazard ratio, 3.809; 95% CI, 2.106–4.531), and lactate greater than or equal to 2 mmol/L (hazard ratio, 1.454; 95% CI, 1.041–2.029) were independently associated with in-hospital mortality. Based on univariate analysis for patients with propensity score matching, dihydropyridine calcium channel blocker (hazard ratio, 2.021; 95% CI, 1.333–3.064), lactate dehydrogenase greater than or equal to 600 U/L (hazard ratio, 4.379; 95% CI, 2.642–7.257), and lactate greater than or equal to 2 mmol/L (hazard ratio, 2.461; 95% CI, 1.534–3.951) were independently associated with in-hospital mortality. In contrast, patients not treated with dihydropyridine calcium channel blocker had a significant survival advantage over those treated with dihydropyridine calcium channel blocker in both patients without or with propensity score matching ( p < 0.001; p = 0.001 by Kaplan-Meier analysis). CONCLUSIONS: Dihydropyridine calcium channel blocker, lactate dehydrogenase greater than or equal to 600 U/L, and lactate greater than or equal to 2 mmol/L at admission were independent risk factors for patients with hypertension and moderate-severe pulmonary acute respiratory distress syndrome.